Online Measurement of Microembolic Signal Burden by Transcranial Doppler during Catheter Ablation for Atrial Fibrillation—Results of a Multicenter Trial - von Bary, Christian; Deneke, Thomas; Arentz, Thomas; Schade, Anja; Lehrmann, Heiko; Fredersdorf, Sabine; Baldaranov, Dobri; Maier, Lars; Schlachetzki, Felix (Frontiers in Neurology, 2017)
Introduction: Left atrial pulmonary vein isolation (PVI) is an accepted treatment option for patients with symptomatic atrial fibrillation (AF). This procedure can be complicated by stroke or silent cerebral embolism (SCE). Online measurement of microembolic signals (MES) by transcranial doppler (TCD) may be useful for characterizing thromboembolic burden during PVI. In this prospective multicenter trial we investigated the burden, characteristics and composition of MES during left atrial catheter ablation using a variety of catheter technologies. Materials and Methods: PVI was performed in a total of 42 patients using the circular-shaped multi-electrode pulmonary vein ablation catheter technology (PVAC) in 23, an irrigated single-tip radiofrequency catheter (IRF) in 14, and the cryoballoon (CB) technology in 5 patients. TCD was used to detect the total MES burden and sustained thromboembolic showers of >30s (TES). During TES, the site of ablation within the left atrium was registered. MES composition was classified manually into “solid”, “gaseous” or “equivocal” by off-line expert assessment. Results: The total MES burden was higher when using IRF compared to CB (2336±1654 vs. 593±231;p=0.007) and showed a tendency towards a higher burden when using IRF compared to PVAC (2336±1654 vs. 1685±2255;p=0.08). TES occurred more often when using PVAC compared to IRF (1.5±2 vs. 0.4±1.3;p=0.04) and most frequently when ablation was performed close to the LSPV. Of the MES, 17.004 (23%) were characterized as definitely solid, 13.204 (18%) as clearly gaseous and 44.366 (59%) as equivocal. Discussion: We investigated the burden and characteristics of MES during left atrial catheter ablation for AF. All ablation techniques applied in this study generated a relevant number of MES. There was a significant difference in total MES burden using IRF compared to CB and a tendency towards a higher burden using IRF compared to PVAC. The highest TES burden was found in the PVAC group, particularly during ablation close to the left superior pulmonary vein (LSPV). The composition of thromboembolic particles was balanced. The impact of MES, TES and composition of thromboembolic particles on neurological outcome needs to be evaluated further. (Clinical Trial Registration: Deutsches Register Klinischer Studien, www.drks-neu.uniklinik-freiburg.de - No. DRKS00003465).